Rancang Bangun Sistem Pelayanan Publik Pada Polsek Padang Barat Berbasis Web Dengan Php Dan Database Mysql - Hadi, Abrar; Putra, Pandu Pratama; Syam, Febrizal Alfarasy; Febriadi, Bayu (LPPM STIKOM Tunas Bangsa, 2023)
Police in the SPKT (Integrated Police Service Center) have a function that serves complaints from people who are involved in criminal acts, namely reports of fraud, robbery, embezzlement, robbery, loss of valuables, and so on. Due to complaints from the public at this time, the community needs fast service at the SPKT section. Because SPKT is the spearhead of the police service in providing services to the community to improve and facilitate the services needed by software. At the West Padang Police, if the community makes a complaint or request to the SPKT (Integrated Police Service Center), officers still use a conventional or un-computerized system the weakness of this system is that it is very possible that during the process there is an error in recording, inaccurate reports made, delays in finding the required data STTLP (Police Report Receipt), the officer must rewrite the book for archiving, then if the public makes a second request the officer must rewrite the applicant's data because it takes a long time to search for data.